KAPASITAS PENGHULU DALAM MEMOBILISASI MODAL SOSIAL PADA PEMBANGUNAN DESA BANGKO PUSAKA, KECAMATAN BANGKO PUSAKO, KABUPATEN ROKAN HILIR PADA TAHUN 2015-2016 - Vicky Nanda Putra; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The capacity of Pemulu in mobilizing social capital in village development in Bangko Pusaka is an attempt by the author to look at the extent of the role of the village head or headman in carrying out his duties in building community resources and in the development of the Bangko Pusaka Village infrastructure. In this case, to see the capacity of the Bangko Pusaka Leader, the writer uses a social capital approach that consists of several principles, namely: Trust, Network, and Norm. The aim of the research is first, to describe the capacity of the first managerial in mobilizing social capital in development in Bangko Pusaka village. Second, Describe the political capacity of the prince in mobilizing social capital in development in Bangko Pusaka Village.The type of research that I use in this case is a type of descriptive research with qualitative analysis methods. Research location in Bangko pusaka village. Interview data collection techniques and documentation. While data analysis is done by qualitative analysis. The author uses triangulation as a technique to check the validity of data. The results of this study indicate that the Managerial Capacity and political capacity of the Bangko Pusaka leaders in general are not good enough. Due to the low level of education and experience of the prince. Likewise social capital (Network, Trust and Norms) The potential is in the Kepenghuluan Bangko Pusaka, except that in this case there is a failure of the leader in mobilizing social capital in the community resulting in problematic development, and community distrust towards the person of the headman.Keywords: Governability, Social Capital, Development.